The relevance of Ibn Khaldun’s agricultural economic thoughts during the Covid-19 pandemic - Khairul Anwar; Novalini Jailani; Dhea Aulia Damayanti (Journal of Islamic Economics, Management, and Business (JIEMB), 2022)
This study aims to identify and analyze the concept of agricultural economics thought by Ibn Khaldun and to find out its relevance during the COVID-19 pandemic. As is known, countries in the world, including Indonesia, have been hit by a humanitarian disaster called the COVID-19 pandemic since 2020 which has caused extraordinary disruptions in various sectors of life, including the economic sector. This research is a type of library research using qualitative methods. The main data of this research are books, journals, essays, and news about the core issue, namely Ibn Khaldun's view on agriculture which is then related to conditions in the era of the covid-19 outbreak. The results show that Ibn Khaldun's thoughts on the agricultural economy and the role of the state in serving the community are still very relevant during the COVID-19 pandemic. Agriculture, according to Ibn Khaldun, is the source of life, and really, during the COVID-19 pandemic, the agricultural sector in general did not create a COVID-19 pandemic.